The Influence of Financial Attitude, Peer Influence, and Financial Technology on Financial Behavior of QRIS Users Among Students at FEBI UIN North Sumatera - M. Rafli Lingga; Nurbaiti Nurbaiti; Purnama Ramadani Silalahi (SENTRALISASI, 2026)
This study investigates how Financial Attitude, Peer Influence, and Financial Technology impact the financial behavior of students utilizing QRIS within the Faculty of Islamic Economics and Business at UIN North Sumatera. A quantitative approach with a causal research design framework was utilized, incorporating 98 participants chosen using the Slovin formula. Multiple linear regression was applied for data analysis. Data was gathered through questionnaires structured on a Likert scale ranging from 1 to 5. The data processing was performed using SPSS version 27. The results demonstrate that each of the factors Financial Attitude, Peer Influence, and Financial Technology positively and significantly affects Financial Behavior. Furthermore, the combined effect of these three variables on Financial Behavior is significant. This finding shows that although QRIS facilitates transactions, students financial behavior is still influenced by their financial attitudes and social environment. Therefore, it is necessary to enhance financial awareness and foster positive financial attitudes, as well as encourage the responsible use of financial technology to prevent consumptive behavior in a cashless era.